Investigating the effect of work life quality and social capital on the organizational commitment - Mahmood Reza Esmeili; Hojat Vahdati; Milad Amraei (Management Science Letters)
This paper studies the work life quality and social capital on the organizational commitment. The primary objective of this research is to identify the effect of the quality of Work Life and social capital on the organizational commitment. The study has accomplished among 240 out of 900 employees of tax affairs organization in Lorestan province. To achieve our goal, nine hypotheses were examined. There are three questionnaires including the quality of work life, social capital, and the organizational commitment. Using structural equation modeling, the study has confirmed that there was a meaningful relationship between the variables of the quality of work life with social capital and organizational commitment; namely affective, continuous, normative. In addition, there is a meaningful relationship between the variable social capital with organizational commitment including affective, continuous, and normative.